Translating English specialized dictionary articles into Danish and Spanish: some reflections - Fuertes-Olivera, Pedro A.; Nielsen, Sandro (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper aims to cast some light on three broad topics. Firstly, it elaborates on the concept of dictionaries as texts. Hence, they are compiled to provide assistance in several situations and are divided into sections that often represent different text types. Secondly, it defends that lexicographic equivalence is a parole phenomenon that is so much influenced by genre and topic conventions that practicing it, e.g. translating bilingual dictionary articles, requires skills that, to the best of our knowledge, have not been described in the lexicographic literature. Thirdly, reflections on the above topics are illustrated with the practice of translating the English dictionary articles of the Accounting Dictionaries into Danish and Spanish. They will allow us to comment on some peculiarities of specialized dictionary translation, i.e. a type of translation that shows some differences with standard text types such as journal articles, books and so on.